Analisis Strategi Bisnis Menggunakan Matriks SWOT dan QSPM (Studi Kasus : Jang.toppoki Pamulang, Tangerang Selatan) - Haya, Faiza Nasywa; Saidah, Zumi; Widyasanti, Asri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The food industry in Indonesia has excellent potential due to its abundant supply and numerous consumers. In the third quarter of 2022, there was a growth increase of 3.57% in the food industry. One popular food among the public is Korean cuisine. Tteokbokki, a long-shaped snack made from rice flour, is particularly favored by Korean food enthusiasts. Jang.toppoki is one of the restaurants that offer Korean dishes, especially tteokbokki, located on Flamboyan Raya AC5/34, Pamulang, South Tangerang. The high market competition has made it increasingly challenging for Jang.toppoki to maintain its performance. The purpose of this research is to determine alternative strategic planning and the priority of business strategies for Jang.toppoki. This study utilizes IFAS, EFAS, SWOT, and QSPM matrix. The IFAS and EFAS matrix indicate that the company has a strong internal environmental condition and a moderate external environmental condition. The IE matrix shows that the company is in a "Growth and Development" position. The alternative strategies derived from the SWOT and QSPM matrix prioritize strengthening Jang.toppoki's branding to avoid easy replacement.